As relações estabelecidas entre a metrópole de Belém e a cidade média de Macapá (AP) - Márcio Douglas Brito Amaral (Confins)
This paper aims to contribute to the knowledge of relationship between metropolis and medium city on Amazon from the analysis of the relationship established between Belém and the medium city of Macapá (capital of Amapá State). More than a concern with spatial relationships, it seeks an analysis of economic dynamics and their geographical consequences as part of general process of production and reproduction of capitalist society in this portion of Brazilian territory. The main argument developed in this paper is that relationships between Belém and Macapá must be understood on the core of the process of concentration and centralization of capital that has reached the country.